Countercyclical taxation and price dispersion - Eric Mayer; Oliver Grimm (University of Würzburg, Department of Economics, 2008)
In this paper, we explore the benefits from a supply-side oriented fiscal tax policy within the framework of a New Keynesian DSGE model. We show that countercyclical tax rules, which are contingent on the observed welfare gap or on the cost-push shock and levied on value added, remarkably reduce the adverse impact of cost-push shocks on welfare. We state that the tax rule establishes a path for the evolution of marginal cost at the firm level that largely prevents built up of price dispersion. We highlight that this tax policy is also effective under a balancedbudget regime. Hence, fiscal policy can disencumber monetary policy in the light of cost-push shocks.
Keywords: E32; E61; E62; 330; Countercyclical fiscal policy; welfare costs; nominal rigidities; Antizyklische Finanzpolitik; Soziale Kosten; Wohlfahrtseffekt; Preisspanne; Dynamisches Gleichgewicht; Ungleichgewichtstheorie; Theorie